2010
DOI: 10.4314/ajfand.v10i1.51482
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient content and acceptability of soybean based complementary food

Abstract: Cereal gruels, starchy roots and tubers continue to form the bulk of staple foods in the world. Though commercial foods of high quality are available, they are unaffordable by much of the world's population. There is need to develop a different approach to offer families the opportunity to feed their infants improved formulations with traditional staples. A study was carried out in Morogoro region, Tanzania, to determine composition and acceptability of soy-based formulations with banana and cowpeas as traditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 7 publications
2
25
0
Order By: Relevance
“…If the porridge has a very low or very high consistency, its acceptability may be low. Some previous studies have found that complementary food formulations with addition of sugar were found to be more tasty and appealing than those without sugar, indicating that inclusion of sugar not only increased the energy density of the porridge but enhanced the taste and characteristic improved flavour (Martin et al, 2010;Muhimbula et al, 2011). Owino et al, 2007 found that sweetness improved the acceptability of α-amylase-treated maize-beans-groundnuts-bambaranuts complementary blends.…”
Section: Discussionmentioning
confidence: 99%
“…If the porridge has a very low or very high consistency, its acceptability may be low. Some previous studies have found that complementary food formulations with addition of sugar were found to be more tasty and appealing than those without sugar, indicating that inclusion of sugar not only increased the energy density of the porridge but enhanced the taste and characteristic improved flavour (Martin et al, 2010;Muhimbula et al, 2011). Owino et al, 2007 found that sweetness improved the acceptability of α-amylase-treated maize-beans-groundnuts-bambaranuts complementary blends.…”
Section: Discussionmentioning
confidence: 99%
“…Testing the acceptability of novel CFs is necessary because it is a measure that can inform whether caregivers will feed the CF to children and whether children will accept to eat the CF (Skinner et al, 2002). However, several studies have used child caregivers to test the acceptability of CFs (Martin, Laswai and Kulwa, 2010;Govender et al, 2014;Amod et al, 2016;Pillay, Khanyile and Siwela, 2018), hence neglecting the target group for CFs, which are children. Such studies argue that they prefer using caregivers to children because children are too young to provide a rational judgement on the sensory attributes such as taste, aroma, colour and texture, usually used to test for acceptability of foods (Martin, Laswai and Kulwa, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The quality of a protein is usually evaluated by comparing its amino acid profile to that of the FAO/WHO/UNU (1985) standard amino acid pattern or by observing the growth performance and nitrogen balance of animals fed on a diet containing legumes as the only protein source. Thus, by combining the protein from legumes and cereals, dietary proteins of high nutritive value similar to protein from meat, fish and egg are obtained due to mutual complementation (Solomon, 2005;Martin et al, 2010). However, one of the militating factors against the use of legume without proper and adequate treatment/processing is its antinutritional factors.…”
Section: Legumesmentioning
confidence: 99%
“…Vitamin A programme have also been demonstrated to reduce mortality rates of under-five years old children in both Africa and Asia (Davidson, 2002;Figueroa & RodriguezGarcia, 2002). The advice to provide pro-vitamin A-rich fruits and vegetables daily is based on the clear health benefits associated with preventing vitamin A deficiency, and the likelihood that consumption of such foods will also help meet the needs for many of the other vitamins (Martin et al, 2010). Micronutrient deficiencies, particularly deficiencies of iodine, iron and vitamin A are major problems for school age children in low-income countries, Nigeria inclusive.…”
Section: Micronutrient Requirementmentioning
confidence: 99%
See 1 more Smart Citation